Evaluación de la producción del cultivo de pepinillo (Cucumis Santibus L.) en función a la aplicación de tres tipos de abonos químicos y un orgánico en el cantón Ibarra provincia de Imbabura - Benitez Morales, Diego (2012)
This research was conducted in the Canton Ibarra, Imbabura Province, in order to assess crop. Production gherkin (Cucumis sativus L.) in relation to the application of three types of organic versus chemical fertilizers; chemical fertilizers Identify or organic most appropriate for the development and performance of the pickle and analyze economically established treatments. The study was applied in the design of randomized complete block (RCB) with five treatments and four replications. The variables were subjected to analysis of variance using the Tukey test at 5% to determine statistical differences of treatments. The following variables were evaluated: days to germination, plant height, days to flowering, days to harvest, number of fruits per plant, length, diameter and weight of fruits and performance. Based on the results obtained it was concluded the following; Using Yoorin chemical fertilizers, Yara Mila, and 18-46-00 DAP in land application, effectively acted in behavior and Gherkin phonological development, increasing flower formation, fruit set, color, fruit weight and tolerance to abiotic factors in the culture.